Investigation of the Quality of Shapura Lake Water, Bhopal, Madhya Pradesh, India - ., Salahuddin (SPC Journal of Environmental Sciences, 2020)
The present study is based on Physico-Chemical Parameter of Shahpura Lake of Bhopal, Madhya Pradesh. The water of Shahpura Lake is polluted due to substantial release of contaminated materials without acceptable treatment to expunge pernicious compounds. The Physico-Chemical parameters such as Chloride(Cl), Total Hardness(TH), Alkalinity(A), pH(pH), Electric Conductivity(EC), Total Dissolved Solids (TDS), Fluoride(F), Iron(Fe), Turbidity(Td), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand(COD) and Sulphate (S)Â were examined to know the present status of the Lake water quality. Statistical analysis like Pearson Correlation matrix and Factor loadings were implemented to the data set to know the relationship among the studied parameters.Â Â Â